2022
DOI: 10.1007/s12035-022-03011-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-proteomic Analysis Revealed Distinct Protein Profiles in Cerebrospinal Fluid of Patients Between Anti-NMDAR Encephalitis NORSE and Cryptogenic NORSE

Abstract: Background: New-onset refractory status epilepticus (NORSE) caused by anti-N-methyl-d-aspartate receptor (anti-NMDAR) encephalitis and cryptogenic etiologies are various in clinical features. The underlying mechanisms of the diseases have still remained elusive.Methods: 6 patients with anti-NMDAR encephalitis NORSE, 5 with cryptogenic NORSE (C-NORSE), and 5 controls were enrolled. Clinical data, including clinical features, cerebrospinal uid (CSF) samples, and cranial images were collected. CSF samples were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…That might also explain the correlation previously reported between the CSF CXCL8 levels and the up-proteomic score that has been presented as a promising indicator for the assessment of the severity of NORSE. 15 Those data and our results suggest the possible benefit of anti-CXCL8 therapy to reduce seizure severity and prevent the development of post-NORSE epilepsy and worse outcomes. Although anti-CXCL8 therapy has not been reported for the treatment of patients with SE, in a mouse model of SE refractory to benzodiazepines, the administration of reparixin, a molecule able to specifically block the activation of CXCR1/CXCR2 by CXCL8, showed a faster SE decay, a reduced incidence of acute symptomatic seizures after SE, and a delayed time to spontaneous seizure onset compared with control animals.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…That might also explain the correlation previously reported between the CSF CXCL8 levels and the up-proteomic score that has been presented as a promising indicator for the assessment of the severity of NORSE. 15 Those data and our results suggest the possible benefit of anti-CXCL8 therapy to reduce seizure severity and prevent the development of post-NORSE epilepsy and worse outcomes. Although anti-CXCL8 therapy has not been reported for the treatment of patients with SE, in a mouse model of SE refractory to benzodiazepines, the administration of reparixin, a molecule able to specifically block the activation of CXCR1/CXCR2 by CXCL8, showed a faster SE decay, a reduced incidence of acute symptomatic seizures after SE, and a delayed time to spontaneous seizure onset compared with control animals.…”
Section: Discussionsupporting
confidence: 70%
“…17,41,42 The increase of CXCL8 levels in the serum of patients with cNORSE found in our study mirrors the recent findings of a multi-protein analysis study that suggested the involvement of the innate and lymphocyte-mediated immune response in cNORSE pathogenesis. 15 Studies have shown that CXCL8 receptors are expressed by neurons and the acute application of CXCL8 to neurons enhanced neuronal excitability by inducing an intracellular calcium elevation and increasing sodium currents. 43,44 Chronic treatment with MIP-1α, a chemokine involved in macrophage and neutrophil recruitment, was also found able to modulate intracellular calcium dynamics and increase hippocampus NMDA receptor levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations